2020
DOI: 10.1016/s0140-6736(20)30166-5
|View full text |Cite
|
Sign up to set email alerts
|

The risk of tuberculosis in children after close exposure: a systematic review and individual-participant meta-analysis

Abstract: Background Tens of millions of children are exposed to Mycobacterium tuberculosis globally every year; however, there are no contemporary estimates of the risk of developing tuberculosis in exposed children. The effectiveness of contact investigations and preventive therapy remains poorly understood.Methods In this systematic review and meta-analysis, we investigated the development of tuberculosis in children closely exposed to a tuberculosis case and followed for incident disease. We restricted our search to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
152
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(202 citation statements)
references
References 23 publications
11
152
1
13
Order By: Relevance
“…1 ), but overall impact on TB incidence and mortality was reduced (Appendix Table S4). If reactivation rates were considered to be age-specific (20% two-year cumulative incidence for children 0–4 years and 10% for children 5–14%) [6] , corresponding ICERs were $154 per DALY averted among children 0–4 years old and $412 per DALY averted among children 5–14 years old.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), but overall impact on TB incidence and mortality was reduced (Appendix Table S4). If reactivation rates were considered to be age-specific (20% two-year cumulative incidence for children 0–4 years and 10% for children 5–14%) [6] , corresponding ICERs were $154 per DALY averted among children 0–4 years old and $412 per DALY averted among children 5–14 years old.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Household contact investigation of individuals diagnosed with active TB can ensure that pediatric household contacts receive prompt treatment (if diagnosed with active TB) or preventive therapy, which can reduce their subsequent risk of morbidity and mortality [ 1 , 5 , 6 ]. The World Health Organization (WHO) recommends contact investigation and symptom-based screening for identifying active TB, plus provision of a short-course regimen for preventive therapy for children in high burden settings [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently shown that TB disease in young children usually occurs soon after exposure and infection, that the risk of disease if infected is high, and that TB preventive therapy (TPT) can significantly reduce the risk of disease following exposure and infection [ 4 ]. A meta-analysis reported that 10% of young child contacts had TB disease at the time of screening, and 35% had evidence of infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children represent a particularly important and interesting population, as although young children are susceptible to disease progression and have high morbidity and mortality, early school-age children appear to be relatively protected against development of tuberculosis, and some children show no signs of disease or asymptomatic infection despite defined exposure to infectious cases of pulmonary tuberculosis [ 5 , 6 ]. Latent tuberculosis infection (LTBI) is a clinically relevant phenotype because the risk of incident tuberculosis is significantly higher in children of all ages with a positive baseline tuberculin skin test (TST) or Interferon Gamma Release Assay (IGRA) compared to those with negative baseline tests [ 7 , 8 ]. Building on paediatric observational data, there is now clinical trial evidence that Bacillus Calmette–Guérin (BCG) vaccine protects against TB infection [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%